Impact of Shifting Subpolar Front on Phytoplankton Dynamics in the Western Margin of East/Japan Sea - Kim, Dongyoung; Ji, Rubao; Park, Hyun Je; Feng, Zhixuan; Jang, Jaebin; Lee, Chung l; Kang, Yun-Ho; Kang, Chang-Keun (Frontiers in Marine Science, 2021)
A subpolar front generated between the East Korea Warm Current (EKWC) and the North Korea Cold Current (NKCC) in the western margin of the East/Japan Sea has shifted northward in recent decades. This study investigated the biomass and composition of the phytoplankton assemblage in relation to hydrological and biogeochemical features in the shallow shelf and slope off the Korean coast from January to June in 2016 and 2017, to determine the mechanistic effects of subpolar front on spring–summer phytoplankton bloom dynamics. Monthly average depth-integrated chlorophyll a (Chl a) levels and the contribution of phytoplankton classes revealed bimodal diatom blooms in early spring and summer in the frontal zone. Canonical correspondence analysis showed that the distribution of high Chl a was associated with cold, low-salinity NKCC water in March 2016. No Chl a peak was observed in March 2017 when the warm saline EKWC water mass invaded. These results suggest that the NKCC intrusion acts as a forcing mechanism leading to enhanced phytoplankton biomass in the frontal zone. In contrast, positive correlations of Chl a concentration with water density and nutrient concentrations suggest that summer blooms were fed by the subsurface chlorophyll maximum (SCM) driven by shoaling of the pycnocline and nitracline. Varying water-column stratification determined the thickness of the SCM layer, driving year-to-year variability in the magnitude of diatom blooms. These findings further suggest that seasonal/interannual variability in the timing of algal blooms affect regional trophodynamics and hence could be an important factor explaining ecosystem changes in this region.